Moral disengagement as a self-regulatory process in sexual harassment perpetration at work: A preliminary conceptualization. (March 2015) - Page, Thomas E.; Pina, Afroditi
Abstract: Sexual harassment is recognized as a widespread form of aggressive behavior with severe consequences for victims and organizations. Yet, contemporary research and theory focusing on the motives and cognition of sexual harassment perpetrators continues to be sparse and underdeveloped. This review examines the motivations that underlie sexual harassment and the self-exonerating cognitions and behavioral techniques employed by perpetrators of sexual harassment. In this paper, we emphasize the need to understand the cognitive processes that disinhibit motivated individuals to sexually harass. Utilizing social cognitive theory as a foundation, we propose that cognitive mechanisms of moral disengagement are likely to have an important etiological role in the facilitation and reinforcement of sexually harassing behavior. A preliminary conceptual framework is presented, suggesting novel ways in which each of the various moral disengagement mechanisms may contribute to sexual harassment perpetration. Highlights: We examine literature on sexual harassment perpetrators and their cognitions and motivations We propose a novel application of Bandura's Moral Disengagement Theory to the sexual harassment context Mechanisms of moral disengagement can have an etiological role in sexual harassment perpetration We outline each moral disengagement mechanism as a cognitive process that regulates sexually harassing behavior